Comparative physicochemical analysis of suspended and immobilized cultivation of Chlorella sp. Issue 2 (23rd April 2012) - Zeng, Xianhai; Danquah, Michael K.; Halim, Ronald; Yang, Shuyu; Chen, Xiao Dong; Lu, Yinghua
Abstract BACKGROUND: Immobilized cultivation of microorganisms is gaining interest in the microalgae industry. In this study, a novel microalgae polymeric carrier, sodium cellulose sulphate/poly‐dimethyl‐diallyl‐ammonium chloride (NaCS‐PDMDAAC) capsule system, was employed to immobilize Chlorella sp. Microalgae cultivation was performed under immobilized and suspended conditions, and the resulting cells were characterized biochemically and physically. RESULTS: Experimental results indicated that microalgae cells cultivated under NaCS‐PDMDAAC immobilized conditions have a robust morphology, a smaller average cell size of 2.92 µm and a higher Zeta potential of − 17.10 mV than the suspended cells with a cell size of 6.81 µm and Zeta potential of − 32.90 mV. The immobilized microalgae cells displayed a total lipid content of 14.85%, and a chlorophyll content of 3.36%, slightly higher than those obtained from the suspended cells. CONCLUSION: These differences are critical to further explore the impact of immobilized microalgae cultivation systems for specific biotechnological applications. © 2012 Society of Chemical Industry